Comparison of the effect of two methods of counseling (face to face and telephone) on awareness and attitude toward adoption in infertile couples - Fateme Ahmadi Rezamahaleh; Talat Khadivzadeh; Seyed Mohsen Asgharinekah; Habibollah Esmaeili (Wolters Kluwer Medknow Publications, 2020)
INTRODUCTION: Many infertile people have heard about adoption, but little is known about the true meaning of adoption and how it is accepted. Giving the right information about adoption is effective in making the right decision for couples. As a result, there is a need to intervene and provide training to improve community attitudes and increase adoption among infertile people. Therefore, the present study aimed to determine the effect of two counseling methods (face-to-face and telephone) on awareness and attitude toward adoption in infertile couples. MATERIALS AND METHODS: The present study is a randomized quasi-experimental study of two groups in the Milad Infertility Center of Mashhad on 34 (each group of 17 couples) infertile couples with the criteria to enter the study. Couples were randomly assigned to two telephone and face-to-face counseling groups, and each individual's awareness and attitudes toward adoption were completed separately before and after counseling. The average number of face-to-face sessions for face-to-face counseling was three 60-min sessions and six 30-min sessions for telephone counseling. RESULTS: Based on the results of t-test, there was a statistically significant difference between the average score of awareness of adoption before and after the intervention (2 weeks after the last counseling session), in infertile couples in face-to-face training group and in telephone training group (P< 0.0001). The score of the attitude toward adoption before counseling in the face-to-face counseling group was 60.55 ± 5.5, which reached 66.76 ± 4.7 after counseling. Based on the results of the T-pair test, this difference was significant (P < 0.0001). In addition, in the telephone counseling group, the score of attitude toward adoption increased from 59.53. 7.4 to 67.73 ± 7.5, which was a significant difference in terms of t-pair test. The mean score of attitudes toward adoption was not statistically significant in the two groups (P = 0.653). CONCLUSION: The results of this study showed that both counseling methods (face to face and telephone) increase the level of awareness and attitude of couples about adoption, but neither method was superior to the other.